2006
DOI: 10.1089/mdr.2006.12.44
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Plasmid-mediated AmpCβ-Lactamases inEscherichia coliandKlebsiella pneumoniaein Korea

Abstract: Cefoxitin-resistant Escherichia coli and Klebsiella pneumoniae are relatively prevalent in Korea, suggesting dissemination of plasmid-mediated AmpC beta-lactamases. In this study, 238 isolates of cefoxitin-resistant E. coli and K. pneumoniae (not including subspecies ozaenae and rhinoscleromatis) were collected in 2003 from 16 Korean hospitals. The prevalence of plasmid-mediated AmpC beta-lactamases was determined by PCR. The AmpC gene alleles detected in E. coli and K. pneumoniae were bla(DHA-1), 10 (8.6%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 23 publications
0
42
2
3
Order By: Relevance
“…The prevalence of PABL producers in this study was found to be 0.13% overall (range, 0.02 to 0.5%). This rate of prevalence was much lower than that reported for other countries, such as Korea (3.1%) (26), China (2.8%) (14), and the United States (1.2%) (8). However, we isolated PABL producers from 13 of 17 laboratories in the Kinki region, suggesting that PABL producers may be on the increase.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The prevalence of PABL producers in this study was found to be 0.13% overall (range, 0.02 to 0.5%). This rate of prevalence was much lower than that reported for other countries, such as Korea (3.1%) (26), China (2.8%) (14), and the United States (1.2%) (8). However, we isolated PABL producers from 13 of 17 laboratories in the Kinki region, suggesting that PABL producers may be on the increase.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition to these enzyme types, DHA-type enzymes have been identified in Taiwan (31) and China (15). In Korea (14,26), DHA-, CMY/MOX-, and ACT-1/MIR-1-type enzymes have also been identified, while in the United States (1,17), in addition to the types mentioned above, DHA-, ACT-1/MIR-1-, and FOX-type enzymes have been identified. To date, in Japan, MOX-1 (11), CMY-9 (9,28), , CFE-1 (19), CMY-2 (18), and DHA-1 (18) have been found in clinical isolates.…”
mentioning
confidence: 94%
“…Many traits that have been shown to be involved in bacterial cooperation and virulence are coded by mobile elements, such as traits that are capable of breaking down toxins in the local environment (Knothe et al, 1983;Philppon et al, 2002;Lee et al, 2006;Ellis et al, 2007) and secreted toxins (O'Brien et al, 1984;Waldor and Mekalanos, 1996;Ahmer et al, 1999). One theoretical study (Smith, 2001) suggested that if cooperation is coded on plasmids, these plasmids will be able to reinstate cooperation by forcing non-producing strains (through infection) to start secreting the extracellular public good (Smith, 2001).…”
Section: Mges As Drivers Of Bacterial Socialitymentioning
confidence: 99%
“…However, the use of antibiotics in treatment of clinical enteric infection has been heavily compromised by emerging multidrug-resistant microbes (4,17,18,23). In particular, resistance due to extended-spectrum ␤-lactamases (ESBLs) and AmpC ␤-lactamases is of special concern as these enzymes confer resistance to some of the front-line antibiotics used to treat enteric infection in humans and animals (4,13,14,19).…”
mentioning
confidence: 99%